Model Comparison Exercise Circuit Training Game and Circuit Ladder Drills to Improve Agility and Speed - Hendrawan, Susilaturochman; Setijino, Hari; Mintarto, Edy (Universitas Negeri Semarang (Unnes), 2017)
The purpose of this study was to compare: (1) the effect of circuit training game and circuit ladder drill for the agility; (2) the effect of circuit training game and circuit ladder drill on speed; (3) the difference effect of circuit training game and circuit ladder drill for the speed (4) the difference effect of circuit training game and circuit ladder drill on agility. The type of this research was quantitative with quasi-experimental methods. The design of this research was Factorial Design, with analysing data using ANOVA. The process of data collection was done by using 30 meters sprint speed test and shuttle run test during the pretest and posttest. Furthermore, the data was analyzed by using SPSS 22.0 series. Result: The circuit training game exercise program and circuit ladder drill were significant to increase agility and speed (sig 0.000 < ? = 0.005) Group I, II, III had significant differences (sig 0.000 < ? = 0.005). The mean of increase in speed of group I = 0.20 seconds, group II = 0.31 seconds, and group III = 0.11 seconds. The average increase agility to group I = 0.34 seconds group II = 0.60 seconds, group III = 0.13 seconds. Based on the analysis above, it could be concluded that there was an increase in the speed and agility of each group after being given a training.